A escola bíblica dominical atuando na provenção do HIV/AIDS: um estudo a partir da Igreja Evangélica Assembleia de Deus - Santana, Sonia Carvalho de (2013)
The objective of this investigation is the Sunday School classes (SS) as a potential place to address and develop prevention to HIV/AIDS. Specific objectives were to know the Evangelical Church Assembly of God (AG), the Sunday School, its curriculum and how HIV and AIDS are /or could be approached in its curriculum content, to reflect the experience in daily affective relations. For this, a survey was conducted of literature descriptive review, exploratory and quantitative literature review about the Church and Sunday School, curriculum content, and prevention to HIV/AIDS. Succinctly facts relating to the historicity of the Assembly of God in Brazil, its origin and theological approaches, as well, as the emphasis on prevention of HIV/AIDS are presented. It also discusses the origin of Sunday School in the world, in Brazil, especially in the Assembly of God, its organizational form, bureaucratic and administrative, with emphasis on the curriculum model and content covered in the various age groups as presented. With this, search to understand the occurrence and focus given to the approach to HIV/AIDS. In general the approach related to the historicity highlights the exponents Daniel Berg and Gunnar Vingren as founders of AG in Brazil. Regarding Sunday School it was observed that its origin came almost with the origin of the church in Brazil. It uses content-oriented curriculum of the Division of Christian Education, available to ages from kindergarten to adult. It uses for this standardized material and printed by Publishing House of Assembly of God, called Lessons / Magazine Sunday School. It encourages the development of SS teachers through meetings and specific courses and/or printed literature. As for the focus given to HIV and AIDS It was observed that the curriculum presented no manifestation related to the performance of the SS regarding prevention. When the approach about the disease occurs, it will be at implying form, in a general context without direct specificity. Thus, it is possible to infer suggestion content for possible approaches.